Healthcare Service Delivery Efficiency: Performance of Gauteng Hospitals. Issue 1 (2014) - Ibewuike, Nwauka Oliver; Weeks, Richard
Abstract There is a general perception that public healthcare service delivery is deteriorating severely, despite government commitments to change this. This dysfunction stems from the cumulative impact of burden of diseases, economic pressures, population surge, and policy and strategy incoherence. The core objective of this qualitative research is to gain insight into the cause‐effects of this sub‐minimal performance, patients' dissatisfaction and the waste of resources in Gauteng's public healthcare sectors. This research used Performance Assessment Tools for quality improvement in Hospitals (PATH) framework and Data Envelopment Analysis (DEA) to evaluate the satisfaction levels, performance and technical efficiencies of public hospitals, which were compared to the private sector. The findings agree that patients' satisfaction is poor, performance technically inefficient and health outcomes unsatisfactory relative to private hospitals. Patients' dissatisfaction level was 76%. Health outcomes such as patients re‐admission within a 28‐day period recorded 20%, 21%, <5% for the district, regional and private hospitals respectively, and PHC health outcome (25%). This performance slack resulted partly from overall poor decision‐making abilities on the use and allocation of resources and the lack of integrated information systems.